EFFECT OF PAXHERBAL BITTERS ON INFLAMMATION AND ANTIOXIDANT STATUS IN MALE WISTAR RATS FED A HIGH FRUCTOSE DIET (FUDMA JOURNAL OF SCIENCES, 2024)
Modern diets are often high in fructose, and this has been associated with increased inflammation and oxidative stress. Herbal remedies like Paxherbal bitters have been suggested as possible remedies. This study aims at determining if the co-administration of Paxherbal bitters could prevent the inflammation and oxidative stress, which occurs when male Wistar rats are fed a high fructose diet. Twenty male Wistar rats, approximately 200g each, were divided into four groups: the control, high fructose diet with fructose water (HFD+FW), HFD+FW with Atorvastatin, and HFD+FW with Paxherbal bitters, groups. After a 28-day experimental period, blood samples were assessed for high-sensitive C-reactive protein (HsCRP), malondialdehyde (MDA), and total antioxidant capacity (TAC), using standard methods. Statistical analysis was done using the SPSS-20 package. Results has shown that rats on the high fructose diet, displayed significantly (P
Keywords: High-fructose diet; Inflammation; Oxidative stress; Metabolic syndrome; Paxherbal bitters